2D and 3D Porphyrinic Covalent Organic Frameworks: The Influence of Dimensionality on Functionality. (21st January 2020) - Meng, Yi; Luo, Yi; Shi, Ji‐Long; Ding, Huimin; Lang, Xianjun; Chen, Wei; Zheng, Anmin; Sun, Junliang; Wang, Cheng
Abstract: The construction of 2D and 3D covalent organic frameworks (COFs) from functional moieties for desired properties has gained much attention. However, the influence of COFs dimensionality on their functionalities, which can further assist in COF design, has never been explored. Now, by selecting designed precursors and topology diagrams, 2D and 3D porphyrinic COFs (2D‐PdPor‐COF and 3D‐PdPor‐COF) are synthesized. By model building and Rietveld refinement of powder X‐ray diffraction, 2D‐PdPor‐COF crystallizes as 2D sheets while 3D‐PdPor‐COF adopts a five‐fold interpenetrated pts topology. Interestingly, compared with 2D‐PdPor‐COF, 3D‐PdPor‐COF showed interesting properties, including 1) higher CO2 adsorption capacity; 2) better photocatalytic performance; and 3) size‐selective photocatalysis. Based on this study, we believe that with the incorporation of functional moieties, the dimensionality of COFs can definitely influence their functionalities. Abstract : 2D gegen 3D : Um den Einfluss von Dimensionalität auf die Funktionalität kovalenter organischer Gerüste (COFs) aufzuzeigen, wurde 2D‐ und 3D‐PdPor‐COF synthetisiert. Die Ergebnisse zeigen, dass 3D‐PdPor‐COF im Vergleich zu 2D‐PdPor‐COF nicht nur eine höhere CO2 ‐Adsorptionskapazität, sondern auch eine bessere photokatalytische Leistungsfähigkeit und Größenselektivität vorweist.